GAMBARAN PELAKSANAAN PERAN PERAWAT DALAM MEMBERIKAN ASUHAN KEPERAWATAN DARI SUDUT PANDANG PASIEN DI RUANG RAWAT INAP INTERNE, BEDAH DAN PARU RSUD SOLOK - Armanda Tri Murti Ningsih (Ensiklopedia of Journal, 2018)
Nurses have a very important role for patients and their profession as providers of nursing care, as clients, providers, comfort providers, educators, coordinators, case managers, communicators, clinical decision making, consultations, medical professionals and reformers. This study discusses the discussion of the role of nurses in providing treatment rooms in inpatient rooms, hospitals and pulmonary hospitals in Solok. This research is descriptive, the sample is taken by comparison of simple random sampling with a total of 53 people. Data was collected by collecting questionnaires with respondents. Research results obtained More than half (67.92%) of respondents took as nurses as nurses, nurses carried out their duties well, most (75.47%) of respondents took nurses as educators, nurses carried out their duties as nurses. role well, More than a few (62.26%) respondents chose as nurses as motivators. To improve the quality of nursing services, nurses must perform their roles well. It is expected by nurses in the internal inpatient room, lungs, hospital surgery, to be approved and increase the role of nurses in providing nursing care (care giver), educator (educator) and as a motivator (motivator). To achieve quality and professional nursing services.Keywords : Implementation, Role of Nurse, Nursing care